Penerapan Keadilan Restoratif Pada Tindak Pidana yang Tidak Memenuhi Syarat Diversi di Indonesia - Sukma, Angki (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Juvenile Justice System must prioritize a restorative justice approach, including by applying Diversion, which can only be carried out if two conditions are met: the punishment is under 7 years and it is not a repeat offender. The purpose of this study is to analyze the application of restorative justice in the Police Republic of Indonesia towards crimes that do not meet the Diversion requirements. This research uses a qualitative method with a normative juridical approach. Secondary data used includes primary, secondary, and tertiary legal materials, with data collection techniques in the form of literature studies. Research instruments include Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and National Police Chief Regulation Number 8 of 2021 concerning Handling Crimes Based on Restorative Justice. The analysis technique used is the deductive method. The results showed that the regulation of the conditions for implementing Diversion caused the principle of restorative justice in the SPPA Law not to be fully implemented. However, the police can still handle juvenile cases that do not meet the Diversion requirements through a restorative justice approach based on National Police Chief Regulation Number 8 of 2021.